2013
DOI: 10.1111/jfpp.12107
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Infrared Drying of Mint Leaves

Abstract: The effects of drying temperature on the drying time, color and thin‐layer drying model were investigated. The moisture ratios changes during the drying time were compared by 38 different mathematical models and evaluated by different statistical criteria such as coefficient of determination (R2), reduced chi‐square (χ2), root mean square error and mean relative percentage error (P). According to the results, drying time was between 18 and 38 min at drying temperatures of 60–80C. The lightness and yellowness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 72 publications
4
31
0
Order By: Relevance
“…; Kocabiyik et al . ), mint (Ertekin and Heybeli, ) and others. There has been some works on drying of apricot, including Togrul and Pehlivan () under open‐air sun, Doymaz (), Faal et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kocabiyik et al . ), mint (Ertekin and Heybeli, ) and others. There has been some works on drying of apricot, including Togrul and Pehlivan () under open‐air sun, Doymaz (), Faal et al .…”
Section: Introductionmentioning
confidence: 99%
“…The infrared drying is particularly suitable for thin layers of material with large surface exposed to radiation. Some studies have reported on the effects of infrared application and/or by a combined infrared-assisted convection process such as apple (Nowak and Lewicki, 2004), pineapple (Ponkham et al 2012), tomato (Corre a et al 2012Kocabiyik et al 2015), mint (Ertekin and Heybeli, 2014) and others. There has been some works on drying of apricot, including Togrul and Pehlivan (2004) under open-air sun, Doymaz (2004), Faal et al (2015 and Dai et al (2015) by hot-air dryers, Fahloul et al (2009) by freeze dryer and Garcia-Martinez et al (2013) by combined hot-air and microwave dryer.…”
Section: Introductionmentioning
confidence: 99%
“…Several agricultural products and by-products have been successfully dried by the infrared application and/or by a combined infrared-assisted convection process such as apple slice (Nowak and Lewicki 2004), onion (Sharma et al 2005), peach (Wang and Sheng 2006), sweet potato (Lin et al 2005), apple pomace (Sun et al 2007), red pepper (Nasiroglu and Kocabiyik 2009), tomato by-products (Ruiz Celma et al 2009), sweet potato (Doymaz 2012) and mint (Ertekin and Heybeli 2013). Several agricultural products and by-products have been successfully dried by the infrared application and/or by a combined infrared-assisted convection process such as apple slice (Nowak and Lewicki 2004), onion (Sharma et al 2005), peach (Wang and Sheng 2006), sweet potato (Lin et al 2005), apple pomace (Sun et al 2007), red pepper (Nasiroglu and Kocabiyik 2009), tomato by-products (Ruiz Celma et al 2009), sweet potato (Doymaz 2012) and mint (Ertekin and Heybeli 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Application of infrared radiation to food processing has gained attention due to its inherent advantages over hot air heating. Several agricultural products and by-products have been successfully dried by the infrared application and/or by a combined infrared-assisted convection process such as apple slice (Nowak and Lewicki 2004), onion (Sharma et al 2005), peach (Wang and Sheng 2006), sweet potato (Lin et al 2005), apple pomace (Sun et al 2007), red pepper (Nasiroglu and Kocabiyik 2009), tomato by-products (Ruiz Celma et al 2009), sweet potato (Doymaz 2012) and mint (Ertekin and Heybeli 2013). However, the infrared drying process of watermelon seed has not been investigated in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Carvone is a major volatile compound present in spearmint essential oil, giving its characteristic odor (Telci, Sahbaz, Yilmaz, & Tugay, ). Spearmint leaves are highly perishable due to its high moisture content (78%–83% wb) (Ertekin & Heybeli, ) and to improve its shelf life, postharvest processing is required. Conventionally, sun drying or hot air (HA) drying is used as a postharvest processing technique to extend the shelf life (Therdthai & Zhou, ).…”
Section: Introductionmentioning
confidence: 99%